The Role of Psychological Stress on Heart Autophagy in Mice With Heart Failure. Issue 9 (November 2017) - Lu, Xiao-Ting; Liu, Xiao-Qiong; Wang, Bo; Sun, Yuan-Yuan; Yang, Rui-Xue; Xing, Yi-Fan; Sun, Ping; Wang, Ying-Bin; Zhao, Yu-Xia
ABSTRACT: Objective: Psychological stress in chronic heart failure (CHF) is associated with systemic neurohormonal and immune system responses and increased mortality. Autophagy refers to the biological process of degradation and recycling of dysfunctional cellular components. We investigated the role of psychological stress on autophagy function in CHF mice. Methods: C57BL/6 mice underwent transverse aortic constriction, with or without combined acoustic and restraint stress, and cardiac function was assessed by echocardiography analysis. Serum corticosterone and angiotensin II (Ang II) were determined using enzyme-linked immunosorbent assay (ELISA). Autophagy and oxidative stress were measured with immunohistochemistry and quantitative polymerase chain reaction, and chloroquine and rapamycin were used to detect autophagy flux. In vivo, cardiomyocytes were cultured with or without Ang II or N -acetylcysteine, and autophagy and oxidative stress were also detected. Results: A 1-week stress exposure significantly increased serum levels of corticosterone and Ang II ( p = .000), increased levels of oxidative stress, induced overt heart failure, and increased mortality ( p = .002). Furthermore, stress exposure unregulated messenger RNA expression of Bcl-2–interacting coiled-coil protein 1 (10.891 [3.029] versus 4.754 [1.713], p = .001), cysteine-rich domain containing beclin-1 interacting (6.403 [1.813] versus 3.653 [0.441], p = .006), and autophagy 7 (111.696 [4.049] versus 6.189 [1.931], p = .017), increased expression of autophagosomal, and decreased clearance of autophagosomes. In vitro, Ang II significantly increased autophagy flux in cultured cardiomyocytes, which could be partly inhibited by N -acetylcysteine. Conclusions: Psychological stress may contribute to the development of CHF by enhancing heart oxidative stress and impairing autophagy flux. Abstract : Supplemental digital content is available in the text.